Pengaruh Komunikasi Pimpinan Terhadap Kinerja Karyawan Pada Badan Pusat Statistik Kabupaten Labuhanbatu - Epa Purnama Sari Harahap; Muhammad Irwan Padli Nasution (LPPM Universitas Labuhanbatu, 2022)
In this study the aim is to find out how the influence of leadership communication on employee performance at the Central Bureau of Statistics in Labuhanbatu Regency. Which is where leadership communication greatly affects employee performance, has an effect on increasing employee morale and provides ideas for developing better BPS agencies. Of the 24 employees who interviewed researchers said that leadership communication affects their morale with BPS leaders who have a caring nature for employees, reminding employees of the work assigned to employees.